Treatment With 2-Pentadecyl-2-Oxazoline Restores Mild Traumatic Brain Injury-Induced Sensorial and Neuropsychiatric Dysfunctions - Boccella, Serena; Iannotta, Monica; Cristiano, Claudia; Iannotti, Fabio Arturo; Bello, Fabio Del; Guida, Francesca; Belardo, Carmela; Infantino, Rosmara; Ricciardi, Flavia; Giannella, Mario; Calignano, Antonio; Di Marzo, Vincenzo; et al. (Frontiers in Pharmacology, 2020)
Traumatic brain injury (TBI) represents an important public health problem and is followed by neuroinflammation and neurological dysfunctions. It has been suggested that brain trauma is often associated to deep behavioral alterations and chronic pain-like syndrome. Despite inducing minimal brain damage, mild TBI (mTBI) leads to persistent behavioral changes, including anxiety, depression, social interaction impairment and aggressiveness. The clinical management of these symptoms is still unsatisfactory and new pharmacological treatments are needed, especially for the aggressiveness and depression. In a mouse model of mTBI, we investigated the effect of 2-Pentadecyl-2-Oxazoline (PEA-OXA), a natural compound, that is a secondary metabolite, found in green and roasted coffee beans, on both the pain perception, and neuropsychiatric dysfunctions. We found that the compound acts as a α2 adrenergic antagonist and this mechanism is here described for the first time. Fourteen-days mTBI mice developed anxious and aggressive behavior, whilst depressive-like behavior and impaired social interactions were observed from the 60th day onward.PEA-OXA normalized all the behavioral changes investigated. We also investigated the memory impairments through Morris Water Maze (MWM) test. Both sham and mTBI mice treated with PEA-OXA showed amelioration in the reversal task of the MWM. Nevertheless, the main symptom of the long-term mTBI is represented by the depressive-like behavior, which was completely reversed by PEA-OXA repeated administration. In humans, mTBI-induced depression precedes the appearance of dementias and is characterized by a massive deficit of GABAergic transmission in the cortices. We found that PEA-OXA normalized the GABA changes in the prefrontal cortex. In order to prove the α2-mediated effect of the PEA-OXA we have performed open field test in naïve animals by microinjecting into the medial prefrontal cortex the dexomedetomidine, a selective α2 agonist with or without PEA-OXA co-injection. We found that PEA-OXA antagonized the α2 agonist effect on the locomotor activity. Moreover, PEA-OXA microinjection into the medial prefrontal cortex induced an enhancement of dopamine release.Collectively, these data suggest that this natural compound, through its multi-target activity is able to: i) ameliorate behavioral alterations (i.e. depression), ii) selectively normalize cortical GABA levels, iii) rescue the impaired neuronal activity in the prefrontal cortex.